The "Ought-Is" Problem: An Implementation Science Framework for Translating Ethical Norms Into Practice. - Sisk, Bryan A.; Mozersky, Jessica; Antes, Alison L.; DuBois, James M. (American Journal of Bioethics, 2020)
We argue that once a normative claim is developed, there is an imperative to effect changes based on this norm. As such, ethicists should adopt an "implementation mindset" when formulating norms, and collaborate with others who have the expertise needed to implement policies and practices. To guide this translation of norms into practice, we propose a framework that incorporates implementation science into ethics. Implementation science is a discipline dedicated to supporting the sustained enactment of interventions. We further argue that implementation principles should be integrated into the development of specific normative claims as well as the enactment of these norms. Ethicists formulating a specific norm should consider whether that norm can feasibly be enacted because the resultant specific norm will directly affect the types of interventions subsequently developed. To inform this argument, we will describe the fundamental principles of implementation science, using informed consent to research participation as an illustration.